2021
DOI: 10.3389/fpsyg.2021.584976
|View full text |Cite
|
Sign up to set email alerts
|

How E-Learning Environmental Stimuli Influence Determinates of Learning Engagement in the Context of COVID-19? SOR Model Perspective

Abstract: The COVID-19 pandemic at the beginning of 2020 has changed the conventional learning mode for most students at schools all over the world, and the e-learning at home has become a new trend. Taking Chinese college students as the research subject and drawing on the stimulus–organism–response (S-O-R) model, this paper examines the relationship between the peer referent, perceived closeness, and perceived control and the learning engagement. Using data from 377 college students who have used e-learning, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 117 publications
(140 reference statements)
5
45
0
Order By: Relevance
“…In a qualitative phenomenological study with five university students in the Philippines, Alvarez (2020) showed how learning engagement and isolation and the lack of affective and emotional support affected learning engagement. Another study (Yang et al, 2021) showed that students' self-efficacy and well-being were positively predicted by their perceived closeness with the teacher, peer influence, and perceived control over own learning. Students' perceived learning outcomes were also found to be positively influenced by instructional support and instructor innovation, and-interestingly-negatively by teacher performance (Wang et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a qualitative phenomenological study with five university students in the Philippines, Alvarez (2020) showed how learning engagement and isolation and the lack of affective and emotional support affected learning engagement. Another study (Yang et al, 2021) showed that students' self-efficacy and well-being were positively predicted by their perceived closeness with the teacher, peer influence, and perceived control over own learning. Students' perceived learning outcomes were also found to be positively influenced by instructional support and instructor innovation, and-interestingly-negatively by teacher performance (Wang et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Relatedness and peer interaction play a crucial role in online environments. Thus, it is not surprising that some recent studies highlighted their importance during the COVID-19 pandemic for life satisfaction in general ( Teuber et al, 2021 ), well-being ( Yang et al, 2021 ), motivation ( Besser et al, 2020 ; Camacho et al, 2021 ), self-regulation ( Zhou et al, 2021 ), and student engagement ( Chiu, 2021 ). However, none of those studies has specifically tested the mediating role of relatedness satisfaction between relatedness support and intrinsic motivation and vitality during online classes.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Therefore, this study will build an SOR model based on the variables of the SCCT model and explore student satisfaction by combining the characteristics of the two models. Scholars believe that the setting of pre-variables will affect the subsequent psychological response of the individuals (Zhai et al, 2020), while most of the stimulus variables studied in the past emphasize the external and internal influences that affect the learning of students in the classroom; thus, the research context focused on classroom level (Yang et al, 2021). However, whether or not the psychological cognitive results will remain the same or similar after students leave the classroom, there is an unsolved black box (Wong, in press).…”
Section: Introductionmentioning
confidence: 99%